Murine cytomegalovirus promotes renal allograft inflammation via Th1/17 cells and IL‐17A. Issue 10 (15th June 2022) - Dhital, Ravi; Anand, Shashi; Graber, Brianna; Zeng, Qiang; Velazquez, Victoria M.; Boddeda, Srinivasa R.; Fitch, James R.; Minz, Ranjana W.; Minz, Mukut; Sharma, Ashish; Cianciolo, Rachel; Shimamura, Masako
Abstract : Human cytomegalovirus (HCMV) infection is associated with renal allograft failure. Allograft damage in animal models is accelerated by CMV‐induced T helper 17 (Th17) cell infiltrates. However, the mechanisms whereby CMV promotes Th17 cell‐mediated pathological organ inflammation are uncharacterized. Here we demonstrate that murine CMV (MCMV)‐induced intragraft Th17 cells have a Th1/17 phenotype co‐expressing IFN‐γ and/or TNF‐α, but only a minority of these cells are MCMV specific. Instead, MCMV promotes intragraft expression of CCL20 and CXCL10, which are associated with recruitment of CCR6 + CXCR3 + Th17 cells. MCMV also enhances Th17 cell infiltrates after ischemia–reperfusion injury, independent of allogeneic responses. Pharmacologic inhibition of the Th17 cell signature cytokine, IL‐17A, ameliorates MCMV‐associated allograft damage without increasing intragraft viral loads or reducing MCMV‐specific Th1 cell infiltrates. Clinically, HCMV DNAemia is associated with higher serum IL‐17A among renal transplant patients with acute rejection, linking HCMV reactivation with Th17 cell cytokine expression. In summary, CMV promotes allograft damage via cytokine‐mediated Th1/17 cell recruitment, which may be pharmacologically targeted to mitigate graft injury while preserving antiviral T cell immunity. Abstract : The authors show that urine cytomegalovirus infection promotes cytokine‐induced recruitment of Th1/17 cells into acutely rejecting murine renal allografts and that pharmacologic inhibition of IL‐17A ameliorates allograft damage without increasing intragraft viral loads.